Influences on the clothing preferences for the workplace of fashion magazine professionals - Aznar, Vicloreza M.
This study sought to determine the clothing preferences of selected professionals in fashion [publications (magazine) business. The aim of the study was to determine what influenced clothing preferences in the workplace and how these affect their clothing choices. The descriptive study utilized a three-part, self administered questionnaire. Likewise, on-line feed of the same questionnaire was made available for those who could not be physically present to answer the questionnaire. Using convenience sampling, respondents were chosen. A total of fifty survey questionnaires were distributed and only 60% participated. The data gathered were analyzed using tables and charts with basic statistical and descriptive analysis to determine the factors that influences their clothing preferences. The study showed respondents with stable earnings spent as much as 5-25%of their annual income on clothing. The clothing preferences for the workplace are influenced b fit, design detail, silhouette, color, and material; external factors such as quality, price, brand and country of origin. Colleagues, designers, celebrities friends, and family influence people's clothing choices for work. There are also influences that affect their clothing choices and these include fashion and trends, comfort, occupation, basic values such as religion, aesthetics and social status. The study will provide information on the different influences and inspirations that affect clothing preferences for work.